A study on the effectiveness of promotional strategies by Multimedia College (MMC KL) on the training provided / Nurhafizah Mohd Hanafiah - Mohd Hanafiah, Nurhafizah (Faculty of Business and Management, 2005)
In business today, promotion is important to all organizations. This is the way companies show their products in the market. A good promotion will give benefits towards the products or services. This study is about promotional strategies done by Multimedia College Kuala Lumpur (MMC KL) for the training programmes the college provides. The objective of this study is to identify the effectiveness of promotional strategies, the level of customer awareness and to find suitable marketing communication tools that can be utilized by MMC KL. Besides that, there are two hypotheses that were tested. After the testing, both hypotheses were accepted. First, the promotional strategies by MMC KL are effective, and secondly, the customers are aware of promotional strategies made by MMC KL. The researcher found that several tools can be used by MMC KL to promote the training programmes. The tools are the Internet, websites, televisions, radios, newspapers, magazines, the MMC's Training Calendar, exhibitions or road shows.